Non-Oil Exports and Manufacturing Sector Growth in an Oil-Rich Country in Africa: Case of Nigeria - Ogunewe, Nwanneka Cynthia; Ananwude, Amalachukwu; Nduka, Dr Joseph Afamefuna (Finance & Economics Review, 2020)
Purpose: This paper presents an analysis of the effect of non-oil exports on the manufacturing sector growth in an oil-rich country in Africa – Nigeria from 1986 to 2018. In clear terms, we evaluated how manufacturing sector capacity utilization is affected by non-oil exports. Methods: The Ordinary Least Square (OLS) estimation technique was applied in estimating the model and was lagged by two years. The long-run relationship was determined using the traditional Johansen co-integration methodology. How manufacturing sector growth is affected by non-oil exports was evaluated using the Granger Causality technique. The Augmented Dicky-Fuller (ADF) and Phillips-Perron tests were applied to check the stationarity properties of the data. Results: The growth in the manufacturing sector in Nigeria has not been significantly affected by non-oil export despite the various non-oil export promotion strategies initiated by the government. Implication: A major implication of the finding is that the cost and access to financial services for non-oil exporters should be reduced or relaxed by the Central Bank of Nigeria. High-interest rates charged by commercial banks and little disbursement characterized by the volume of commercial banks credit affect manufacturing firms concerning acquiring modern plants and machinery which results in a poor quality of non-oil exports.